The Quality Changes of Milkfish (Chanos chanos Forsk.) as Influenced by Different Heat Processing Methods - Eko Nurcahya Dewi; Lukita Purnamayati; Retno Ayu Kurniasih (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Milkfish (Chanos chanos Forsk.) contain high protein, particularly lysine as an essential amino acid and Polyunsaturated Fatty Acid (PUFA). High temperature processing namely frying, steaming, and high pressure steaming will reduce the quality of protein and lipid. The aimed of this study was to determine the quality of protein and lipid of milkfish in different processing methods. Samples processed in the form of fried,steamed, and steamed in high pressure milkfish and fresh milkfish as control. Furthermore, the parameters are moisture content, dissolved protein, lysine, free fatty acids, functional groups, and microstructure. The results demonstrated different treatments significantly affected the decreased in the protein and PUFA quality of milkfish. Frying process of milkfish led to significant changes in moisture content, dissolved protein,lysine and the free fatty acids. Fried milkfish had lowest moisture content, dissolved protein, lysine, and free fatty acid were as followed 34.95%, of 0.70%, 1.65% and 6.71%, respectively. The frying process decreased the quality of milkfish protein however did not produce trans fatty acids based on functional group analysis using Fourier Transform Infra-Red (FTIR). The different heating process resulted in the changed of milkfish muscle’s structure. The structure of fresh and steamed milkfish muscle was more compact than milkfish steamed in high pressure product.